Penerapan Algoritma Genetika Dalam Penyebaran Optimasi Jaringan - Sabrina Aisha Putri Lubis; Yahfizham Yahfizham (International Forum of Researchers and Lecturers, 2024)
A network is a system in which computing devices are connected to each other and can share data and resources. To establish a connection, these network devices follow certain rules called communication protocols, both through physical and wireless technology. The performance level of a Wi-Fi network, for example inside a building, can be measured by how well users receive the Wi-Fi signal. The goal of this network is to establish timely and precise communication between users and data senders. A successful Internet connection often depends on receiving a strong and consistent signal, while a fluctuating or weak signal is undesirable. A commonly used approach to measure the average Wi-Fi signal level in a building without needing to understand every detail of the building layout is to use Single Slope Modeling (1SM). This model bases its calculations on the distance between the sending and receiving devices, so it can be used to analyze the performance of Wi-Fi networks, as is done in the case of educational institution buildings. Apart from that, in an effort to optimize network performance, a genetic algorithm was also created which was implemented using the PHP language. This algorithm is based on the principles of genetic algorithms to overcome optimization problems that may arise in the context of such networks.